Teacher Learning and Development The Mirror Maze - Aubusson, Peter (Self-Study of Teaching and Teacher Education Practices, 2006)
This book synthesises current practice and research developments from internationally recognised scholars and practitioners, to provide theoretical and practical knowledge which informs teacher education, development and professional learning. Sections in the book include: the role and significance of learning relationships; emerging dilemmas and challenges; and processes of self-study in teacher education. Throughout the book, self-study contributions highlight the complexity, challenges, struggles, solutions and successes in teacher education experience. They foreshadow exciting developments for further research. Accordingly, the book is likely to appeal to a wide audience of educators - including education academics, teachers, student teachers and researchers.